Preoperative cognition predicts clinical stroke/TIA and mortality after surgical aortic valve replacement in older adults. Issue 8 (14th September 2022) - Simone, Stephanie M.; Price, Catherine C.; Floyd, Thomas F.; Fanning, Molly; Messé, Steven R.; Drabick, Deborah A. G.; Giovannetti, Tania
ABSTRACT: Stroke and death remain risks of surgical aortic valve replacement (SAVR). Preoperative cognitive screeners repeatedly show that reduced scores predict postoperative outcome, but less is known about comprehensive neuropsychological measures predicting risk. This study had two aims: 1) investigate whether preoperative cognitive measures predicted postoperative clinical stroke/transient ischemic attack (TIA) and mortality in older adults undergoing SAVR, and 2) identify the best predictors within a comprehensive cognitive protocol. A total of 165 participants aged 65 + with moderate-to-severe aortic stenosis completed a comprehensive cognitive test battery preoperatively. Postoperative stroke evaluations were conducted by trained stroke neurologists preoperatively and postoperatively, and mortality outcomes were obtained by report and records. Logistic regressions were conducted to evaluate preoperative cognitive predictors of clinical stroke/TIA within 1 week of surgery and mortality within 1 year of surgery. Multivariate models showed measures of delayed verbal memory recall (OR = 0.86; 95% CI 0.74–0.99) and visuospatial skills (OR = 0.95; 95% CI 0.90–1.01) predicted clinical stroke/TIA within 1 week of surgery, R 2 = .41, p < .001, ƒ 2 = .69. Measures of naming ability (OR = 0.88; 95% CI 0.80–0.96), verbal memory recall (OR = 1.23; 95% CI 0.99–1.51), visual memory recall (OR = 0.90; 95% CI 0.80–1.00), medical comorbidities (OR = 1.71; 95% CI 1.22–2.65), and sex (OR = 2.39; 95% CI 0.90–7.04) were significant predictors of death within 1 year of surgery, R 2 = .68, p < .001, ƒ 2 = 2.12. Preoperative cognitive measures reflecting temporal and parietal lobe functions predicted postoperative clinical stroke/TIA within 1 week of SAVR and mortality within 1 year of SAVR. As such, cognitive measures may offer objective and timely indicators of preoperative health, specifically vulnerabilities in cerebral hypoperfusion, which may inform intervention and/or intensive postoperative monitoring and follow-up after SAVR.